The Medial Collateral Ligament in Primary Total Knee Arthroplasty: Anatomy, Biomechanics, and Injury. Issue 12 (15th June 2020) - Cheung, Amy; Yan, Chun Hoi; Chan, Ping Keung; Chiu, Kwong Yuen
Abstract : Understanding the anatomy and biomechanics of the medial collateral ligament (MCL) is crucial in producing good outcomes after total knee arthroplasty. A solid grasp of the surgical techniques that address the MCL are necessary to ensure good coronal plane ligament balance. Furthermore, intraoperative injury to the MCL in total knee arthroplasty is an uncommon yet serious complication which often goes unrecognized. Loss of the integrity of the MCL can lead to instability, loosening, and accelerated polyethylene wear. There is still controversy regarding the ideal method of treatment of intraoperative MCL injuries with suggested treatment modalities ranging from conservative management to use of varus-valgus constrained implants.